2018
DOI: 10.3389/fnagi.2017.00435
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Levels of Akt Activation by PDK1 Knock-in Mutation Protects Neuronal Cultures against Synthetic Amyloid-Beta Peptides

Abstract: The Akt kinase has been widely assumed for years as a key downstream effector of the PI3K signaling pathway in promoting neuronal survival. This notion was however challenged by the finding that neuronal survival responses were still preserved in mice with reduced Akt activity. Moreover, here we show that the Akt signaling is elevated in the aged brain of two different mice models of Alzheimer Disease. We manipulate the rate of Akt stimulation by employing knock-in mice expressing a mutant form of PDK1 (phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 82 publications
(98 reference statements)
0
37
0
Order By: Relevance
“…Moreover, we recently observed that uPAR drives a glycolytic phenotype in melanoma cells [25], triggering a Warburg phenotype mediated by the complex α5β1-integrin-uPAR-EGFR. By using siRNA targeting uPAR, we also previously demonstrated a downregulation of PDK1, which normally promotes the phosphorylation of Akt [36,37]. The inhibition of PDK1 not only inhibits the glycolytic profile of cancer cells, but its downregulation may also be responsible for the enhancement of the spare respiratory capacity observed in uPAR KO cancer cells.…”
Section: Discussionmentioning
confidence: 82%
“…Moreover, we recently observed that uPAR drives a glycolytic phenotype in melanoma cells [25], triggering a Warburg phenotype mediated by the complex α5β1-integrin-uPAR-EGFR. By using siRNA targeting uPAR, we also previously demonstrated a downregulation of PDK1, which normally promotes the phosphorylation of Akt [36,37]. The inhibition of PDK1 not only inhibits the glycolytic profile of cancer cells, but its downregulation may also be responsible for the enhancement of the spare respiratory capacity observed in uPAR KO cancer cells.…”
Section: Discussionmentioning
confidence: 82%
“…The Akt (protein kinase B) signaling pathway is involved in both aging and AD. Aged brains were found to be associated with an imbalance of phosphatidylinositide 3‐kinases (PI3k)/Akt signaling (Jackson, Rani, Kumar, & Foster, ; Jiang, Yin, Yao, Brinton & Cadenas, ; Yang et al, ). In addition to the alteration of PI3K/Akt signaling in the aged brain, increased Akt phosphorylation is also observed in other aging tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated death of prion-infected mice with Aβ deposition might be due to the occurrence of mixed pathologies, that are prion disease and CAA 11 . In any case, inhibiting PDK1 counteracts the toxicity of both prion and transmitted Aβ seeds as BX912 infusion in prion-infected APP23 mice not only reduces the load of PrP Sc , but also the brain deposition of Aβ, which thus reinforces the critical role of PDK1 in amyloid-based neurodegenerative diseases 23,24,57,58 .…”
Section: Discussionmentioning
confidence: 81%